Parents' perceptions of distance learning during COVID-19 in rural Indonesia - Delipiter Lase; Trisa Genia Chrisantiana Zega; Dorkas Orienti Daeli; Sonny Eli Zaluchu (Intelektual Pustaka Media Utama, 2022)
This study was developed to investigate parents' perceptions and attitudes towards distance learning in response to many schools' closures due to the COVID-19. This research employed a qualitative approach. The research subjects consisted of parents of elementary school students in the City of Gunungsitoli, Indonesia determined by purposive sampling technique, totaling twenty-four people. The data were collected using semi-structured interview techniques and analyzed using thematic analysis techniques. This study shows that distance learning or learning from home in a research context takes the form of online and offline learning. The learning approach implemented during the COVID-19 emergency must be lived and supported without other options for parents. Although parents do not have negative perceptions, distance learning has increased the economic, psychological, and social burden on parents or families. The lack of parental involvement and support in children's learning process at home is generally due to the lack of time and parents' inability to become teachers for their children. Actions to accompany and support children's learning process at home are carried out to provide internet packages, help children master the material, and participate in completing assignments or tests given by the teacher. The surprising finding from this study is the decline in children's learning motivation and cognitive abilities. Parents hope that distance learning is not extended.